Enhanced cardiac substructure sparing through knowledge-based treatment planning for non-small cell lung cancer radiotherapy - Momin, Shadab; Wolf, Jonathan; Roper, Justin; Lei, Yang; Liu, Tian; Bradley, Jeffrey D.; Higgins, Kristin; Yang, Xiaofeng; Zhang, Jiahan (Frontiers in Oncology, 2022)
Radiotherapy (RT) doses to cardiac substructures from the definitive treatment of locally advanced non-small cell lung cancers (NSCLC) have been linked to post-RT cardiac toxicities. With modern treatment delivery techniques, it is possible to focus radiation doses to the planning target volume while reducing cardiac substructure doses. However, it is often challenging to design such treatment plans due to complex tradeoffs involving numerous cardiac substructures. Here, we built a cardiac-substructures-based knowledge-based planning (CS-KBP) model and retrospectively evaluated its performance against a cardiac-based KBP (C-KBP) model and manually optimized patient treatment plans. CS-KBP/C-KBP models were built with 27 previously-treated plans that preferentially spare the heart. While the C-KBP training plans were created with whole heart structures, the CS-KBP model training plans each have fifteen cardiac substructures (coronary arteries, valves, great vessels, and chambers of the heart). CS-KBP training plans reflect cardiac-substructure sparing preferences. We evaluated both models on 28 additional patients. Three sets of treatment plans were compared: (1) manually-optimized, (2) C-KBP model-generated, and (3) CS-KBP model-generated. Plans were normalized to receive the prescribed dose to at least 95% of the PTV. A two-tailed paired-sample t-test was performed for clinically relevant dose-volume-metrics to evaluate the performance of the CS-KBP model against the C-KBP model and clinical plans, respectively. Overall results show significantly improved cardiac substructures sparing by CS-KBP in comparison to C-KBP and clinical plans. For instance, average left anterior descending artery volume receiving 15Gy (V15Gy) was significantly lower (p<0.01) for CS-KBP (0.69±1.57cc) compared to clinical plans (1.23±1.76cc) and C-KBP plans (1.05±1.68cc). In conclusion, the CS-KBP model significantly improved cardiac-substructure sparing without exceeding tolerances of other OARs or compromising PTV coverage.